THE INFLUENCE OF ISL AMI WORK ETHICS, LEADERSHIP, AND COMPENSATION ON EMPLOYEE PERFORMANCE WITH JOB SATISFACTION AS AN INTERVENING VARIABLE AT PT BANK MUAMALAT KCU MEDAN BALAIKOTA - Dinda Clarita Wirani Putri; Nurlaila Nurlaila; Muhammad Arif (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2024)
Employee performance is one of the important factors in a company in achieving its goals. The purpose of this study was to test and analyze the influence of Islamic work ethics, leadership, and compensation on employee performance with job satisfaction as an intervening variable at PT Bank Muamalat KCU Medan Balaikota. This research method is quantitative research using data analysis techniques, namely Structural Equation Modeling (SEM) with the Path Analysis method. The analysis test tool used is SmartPLS v.4.0. The isample in this istudy amounted to 80 respondents who were all employees at Bank Muamalat KCU Medan Balaikota. The results of this study show that Islamic work ethics have a significant effect on performance, leadership has a significant effect on performance, compensation affects employee performance, job satisfaction does not affect performance, Islamic work ethics affect job satisfaction, leadership does not affect job satisfaction, compensation affects job satisfaction, and job satisfaction does not mediate the influence of Islamic work ethics, leadership, and compensation on employee performance.